Becoming Slav, becoming Croat : identity transformations in post-Roman and early medieval Dalmatia - Džino, Danijel, 1971- (Leiden : Brill, 2010)
Late antique identities from the Western Balkans were transformed into new, Slavic identities after c. 600 AD. It was a process that is still having continuous impact on the discursive constructions of ethnic and regional identities in the area. Building on the new ways of reading and studying available sources from late antiquity and the early Middle Ages, the book explores the appearance of the Croats in early medieval Dalmatia (the southern parts of modern-day Croatia, Bosnia and Herzegovina). The appearance of the early medieval Croat identity is seen as a part of the wider process of identity-transformations in post-Roman Europe, the ultimate result of the identity-negotiation between the descendants of the late antique population and the immigrant groups.
1., Croat Origins In The Croatian Imagination -- 2., Theoretical Framework And The Scholarship --3., Identities Before The Slavs -- 4., Illyricum And Dalmatia 378–600 : A Very Brief Overview -- 5., Written Sources On The Slav Migration In The 6th And 7th Centuries In Western Illyricum And Dalmatia -- 6., The “Dark Ages”: 7th And 8th Century In Post-Roman Dalmatia I (Cemeteries) -- 7., The “Dark Ages”: 7th And 8th Century In Post-Roman Dalmatia II (Becoming Slavs) -- 8., The Ninth Century: Chroati Ex Machina
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 5.-9. století; Slované; Chorvaté; etnicita -- Chorvatsko -- 5.-9. století; sociální identita -- Chorvatsko -- 5.-9. století; sociální změna -- Chorvatsko -- 5.-9. století; Slavs; Croats; ethnicity -- Croatia -- 5th-9th centuries; social identity -- Croatia -- 5th-9th centuries; social change -- Croatia -- 5th-9th centuries; Dalmácie (Chorvatsko) -- dějiny -- 5.-9. století; Dalmatia (Croatia) -- history -- 5th-9th centuries; e-knihy online; monografie; e-books online; monographs